# Deriving Array Rules

One of the goals of the ChainRules interface is to make it easy to define your own rules for a function. This tutorial attempts to demystify deriving and implementing custom rules for arrays with real and complex entries, with examples. The approach we use is similar to the one succinctly explained and demonstrated in [Giles2008] and its extended work [Giles2008ext], but we generalize it to support functions of multidimensional arrays with both real and complex entries.

Throughout this tutorial, we will use the following type alias:

const RealOrComplex = Union{Real,Complex}

## Forward-mode rules

### Approach

Consider a function

Ω = f(X::Array{<:RealOrComplex}...)::Array{<:RealOrComplex}

or in math notation

$$$f: (\ldots, X_m, \ldots) \mapsto \Omega,$$$

where the components of $X_m$ are written as $(X_m)_{i,\ldots,j}$. The variables $X_m$ and $\Omega$ are intermediates in a larger program (function) that, by considering only a single real input $t$ and real output $s$ can always be written as

$$$t \mapsto (\ldots, X_m, \ldots) \mapsto \Omega \mapsto s,$$$

where $t$ and $s$ are real numbers. If we know the partial derivatives of $X_m$ with respect to $t$, $\frac{dX_m}{dt} = \dot{X}_m$, the chain rule gives the pushforward of $f$ as:

$$$\begin{equation} \label{pf} \dot{\Omega} = f_*(\ldots, \dot{X}_m, \ldots) = \sum_m \sum_{i, \ldots, j} \frac{\partial \Omega}{ \partial (X_m)_{i,\ldots,j} } (\dot{X}_m)_{i,\ldots,j} \end{equation}$$$

That's ugly, but in practice we can often write it more simply by using forward mode rules for simpler functions, as we'll see below. The forward-mode rules for arrays follow directly from the usual scalar chain rules.

Ω = A + B

This one is easy:

$$$\Omega = A + B$$$$$$\dot{\Omega} = \dot{A} + \dot{B}$$$

We can implement the frule in ChainRules's notation:

function frule(
(_, ΔA, ΔB),
::typeof(+),
A::Array{<:RealOrComplex},
B::Array{<:RealOrComplex},
)
Ω = A + B
∂Ω = ΔA + ΔB
return (Ω, ∂Ω)
end

### Matrix multiplication

Ω = A * B
$$$\Omega = A B$$$

First we write in component form:

$$$\Omega_{ij} = \sum_k A_{ik} B_{kj}$$$

Then we use the product rule to get the pushforward for each scalar entry:

\begin{align*} \dot{\Omega}_{ij} &= \sum_k \left( \dot{A}_{ik} B_{kj} + A_{ik} \dot{B}_{kj} \right) && \text{apply scalar product rule } \frac{d}{dt}(x y) = \frac{dx}{dt} y + x \frac{dy}{dt} \\ &= \sum_k \dot{A}_{ik} B_{kj} + \sum_k A_{ik} \dot{B}_{kj} && \text{split sum} \end{align*}

But the last expression is just the component form of a sum of matrix products:

$$$\begin{equation}\label{diffprod} \dot{\Omega} = \dot{A} B + A \dot{B} \end{equation}$$$

This is the matrix product rule, and we write its frule as

function frule(
(_, ΔA, ΔB),
::typeof(*),
A::Matrix{<:RealOrComplex},
B::Matrix{<:RealOrComplex},
)
Ω = A * B
∂Ω = ΔA * B + A * ΔB
return (Ω, ∂Ω)
end

### Matrix inversion

Ω = inv(A)
$$$\Omega = A^{-1}$$$

It's easiest to derive this rule from either of the two constraints:

\begin{align*} \Omega A &= A^{-1} ~A = I\\ A \Omega &= A~ A^{-1} = I, \end{align*}

where $I$ is the identity matrix.

We use the matrix product rule to differentiate the first constraint:

$$$\dot{\Omega} A + \Omega \dot{A} = 0$$$

Then, right-multiply both sides by $A^{-1}$ to isolate $\dot{\Omega}$:

\begin{align} 0 &= \dot{\Omega}~ A~ A^{-1} + \Omega ~\dot{A}~ A^{-1} \nonumber\\ &= \dot{\Omega}~ I + \Omega ~\dot{A}~ A^{-1} && \text{use } A~ A^{-1} = I \nonumber\\ &= \dot{\Omega} + \Omega \dot{A} \Omega && \text{substitute } A^{-1} = \Omega \nonumber\\ \dot{\Omega} &= -\Omega \dot{A} \Omega && \text{solve for } \dot{\Omega} \label{invdiff} \end{align}

We write the frule as

function frule((_, ΔA), ::typeof(inv), A::Matrix{<:RealOrComplex})
Ω = inv(A)
∂Ω = -Ω * ΔA * Ω
return (Ω, ∂Ω)
end

### Other useful identities

These identities are particularly useful:

\begin{align*} \frac{d}{dt} \left( \Re(A) \right) &= \Re(\dot{A})\\ \frac{d}{dt} \left( A^* \right) &= \dot{A}^*\\ \frac{d}{dt} \left( A^\mathsf{T} \right) &= \dot{A}^\mathsf{T}\\ \frac{d}{dt} \left( A^\mathsf{H} \right) &= \dot{A}^\mathsf{H}\\ \frac{d}{dt} \left( \sum_{j} A_{i \ldots j \ldots k} \right) &= \sum_{j} \dot{A}_{i \ldots j \ldots k}, \end{align*}

where $\cdot^*$ is the complex conjugate (conj), and $\cdot^\mathsf{H} = \left(\cdot^\mathsf{T}\right)^*$ is the conjugate transpose (the adjoint function).

## Reverse-mode rules

### Approach

Reverse-mode rules are a little less intuitive, but we can re-use our pushforwards to simplify their derivation. Recall our program:

$$$t \mapsto (\ldots, X_m, \ldots) \mapsto \Omega \mapsto s,$$$

At any step in the program, if we have intermediates $X_m$, we can write down the derivative $\frac{ds}{dt}$ in terms of the tangents $\dot{X}_m = \frac{dX_m}{dt}$ and adjoints $\overline{X}_m = \frac{\partial s}{\partial X_m}$

\begin{align*} \frac{ds}{dt} &= \sum_m \Re\left( \sum_{i,\ldots,j} \left( \frac{\partial s}{\partial (X_m)_{i,\ldots,j}} \right)^* \frac{d (X_m)_{i,\ldots,j}}{dt} \right)\\ &= \sum_m \Re\left( \sum_{i,\ldots,j} (\overline{X}_m)_{i,\ldots,j}^* (\dot{X}_m)_{i,\ldots,j} \right)\\ &= \sum_m \Re\ip{ \overline{X}_m }{ \dot{X}_m }, \end{align*}

where $\Re(\cdot)$ is the real part of a number (real), and $\ip{\cdot}{\cdot}$ is the Frobenius inner product (LinearAlgebra.dot). Because this equation follows at any step of the program, we can equivalently write

$$$\frac{ds}{dt} = \Re\ip{ \overline{\Omega} }{ \dot{\Omega} },$$$

which gives the identity

$$$\begin{equation} \label{pbident} \Re\ip{ \overline{\Omega} }{ \dot{\Omega} } = \sum_m \Re\ip{ \overline{X}_m }{ \dot{X}_m }. \end{equation}$$$

For matrices and vectors, $\ip{A}{B} = \tr(A^\mathsf{H} B)$, and the identity simplifies to:

$$$\begin{equation} \label{pbidentmat} \Re\left( \tr\left( \overline{\Omega}^\mathsf{H} \dot{\Omega} \right) \right) = \sum_m \Re \left( \tr \left( \overline{X}_m^\mathsf{H} \dot{X}_m \right) \right), \end{equation}$$$

where $\tr(\cdot)$ is the matrix trace (LinearAlgebra.tr) function. However, it is often cleaner and more general to work with the inner product.

Our approach for deriving the adjoints $\overline{X}_m$ is then:

1. Derive the pushforward ($\dot{\Omega}$ in terms of $\dot{X}_m$) using \eqref{pf}.
2. Substitute this expression for $\dot{\Omega}$ into the left-hand side of \eqref{pbident}.
3. Manipulate until it looks like the right-hand side of \eqref{pbident}.
4. Solve for each $\overline{X}_m$.

Note that the final expressions for the adjoints will not contain any $\dot{X}_m$ terms.

Note

Why do we conjugate, and why do we only use the real part of the dot product in \eqref{pbident}? Recall from Complex Numbers that we treat a complex number as a pair of real numbers. These identities are a direct consequence of this convention. Consider $\frac{ds}{dt}$ for a scalar function $f: (x + i y) \mapsto (u + i v)$:

\begin{align*} \frac{ds}{dt} &= \Re\ip{ \overline{x} + i \overline{y} }{ \dot{x} + i \dot{y} } \\ &= \Re\left( \left( \overline{x} + i \overline{y} \right)^* \left( \dot{x} + i \dot{y} \right) \right) \\ &= \Re\left( \left( \overline{x} - i \overline{y} \right) \left( \dot{x} + i \dot{y} \right) \right) \\ &= \Re\left( \left( \overline{x} \dot{x} + \overline{y} \dot{y} \right) + i \left( \overline{x} \dot{y} - \overline{y} \dot{x} \right) \right)\\ &= \overline{x} \dot{x} + \overline{y} \dot{y}\\ \end{align*}

which is exactly what the identity would produce if we had written the function as $f: (x, y) \mapsto (u, v)$.

### Useful properties of the inner product

Several properties of the Frobenius inner product come in handy. First, it is linear in its second argument and conjugate linear in its first. That is, for arrays $A, B, C, D$ and scalars $a$ and $b$,

\begin{align} \ip{A+B}{C+D} &= \ip{A}{C} + \ip{B}{C} + \ip{A}{D} + \ip{B}{D} \label{iplinear}\\ \ip{aA}{bB} &= a^* b \ip{A}{B} \nonumber \end{align}

Second, swapping arguments is equivalent to conjugating the inner product:

$$$\begin{equation} \ip{A}{B} = \ip{B}{A}^* \label{ipconj} \end{equation}$$$

Third, for matrices and vectors $A$, $B$, and $C$, we can move arguments from the left or right of one side to the other using the matrix adjoint:

$$$\begin{equation} \ip{A}{BCD} = \ip{B^\mathsf{H} A}{CD} = \ip{B^\mathsf{H} A D^\mathsf{H}}{C} \label{ipperm} \end{equation}$$$

Fourth, the inner product of two arrays $A$ and $B$ is equivalent to the sum of the elementwise inner products of the two arrays:

$$$\begin{equation} \ip{A}{B} = \sum_{i,\ldots,k} \ip{A_{i,\ldots,k}}{B_{i,\ldots,k}} = \sum_{i,\ldots,k} A_{i,\ldots,k}^* B_{i,\ldots,k} \end{equation}$$$

As a result, only elements that are nonzero on both sides contribute to the inner product. This property is especially useful when deriving rules involving structurally sparse arrays.

Now let's derive a few pullbacks using this approach.

### Matrix multiplication

Ω = A * B

We above derived in \eqref{diffprod} the pushforward

$$$\dot{\Omega} = \dot{A} B + A \dot{B}$$$

Using \eqref{pbidentmat}, we now multiply by $\overline{\Omega}^\mathsf{H}$ and take the real trace:

\begin{align*} \Re\ip{\overline{\Omega}}{\dot{\Omega}} &= \Re \ip{\overline \Omega}{\dot{A} B + A \dot{B}} && \text{substitute } \dot{\Omega} \text{ from } \eqref{diffprod}\\ &= \Re \ip{\overline \Omega}{\dot{A} B} + \Re \ip{\overline \Omega}{A \dot{B}} && \text{expand using } \eqref{iplinear} \\ &= \Re \ip{\overline \Omega B^\mathsf{H}}{\dot{A}} + \Re \ip{A^\mathsf{H} \overline \Omega}{\dot{B}} && \text{rearrange the left term using } \eqref{ipperm}\\ &= \Re \ip{\overline A}{\dot{A}} + \Re \ip{\overline B}{\dot{B}} && \text{right-hand side of } \eqref{pbidentmat} \end{align*}

That's it! The expression is in the desired form to solve for the adjoints by comparing the last two lines:

$$$\overline A = \overline \Omega B^\mathsf{H}, \qquad \overline B = A^\mathsf{H} \overline \Omega$$$

Using ChainRules's notation, we would implement the rrule as

function rrule(::typeof(*), A::Matrix{<:RealOrComplex}, B::Matrix{<:RealOrComplex})
function times_pullback(ΔΩ)
∂A = @thunk(ΔΩ * B')
∂B = @thunk(A' * ΔΩ)
return (NoTangent(), ∂A, ∂B)
end
return A * B, times_pullback
end

### Matrix inversion

Ω = inv(A)

In \eqref{invdiff}, we derived the pushforward as

$$$\dot{\Omega} = -\Omega \dot{A} \Omega$$$

Using \eqref{pbidentmat},

\begin{align*} \Re\ip{\overline{\Omega}}{\dot{\Omega}} &= \Re\ip{\overline{\Omega}}{-\Omega \dot{A} \Omega} && \text{substitute } \eqref{invdiff}\\ &= \Re\ip{-\Omega^\mathsf{H} \overline{\Omega} \Omega^\mathsf{H}}{\dot{A}} && \text{rearrange using } \eqref{ipperm}\\ &= \Re\ip{\overline{A}}{\dot{A}} && \text{right-hand side of } \eqref{pbidentmat} \end{align*}

we can now solve for $\overline{A}$:

$$$\overline{A} = -\Omega^\mathsf{H} \overline{\Omega} \Omega^\mathsf{H}$$$

We can implement the resulting rrule as

function rrule(::typeof(inv), A::Matrix{<:RealOrComplex})
Ω = inv(A)
function inv_pullback(ΔΩ)
∂A = -Ω' * ΔΩ * Ω'
return (NoTangent(), ∂A)
end
return Ω, inv_pullback
end

## A multidimensional array example

We presented the approach for deriving pushforwards and pullbacks for arrays of arbitrary dimensions, so let's cover an example. For multidimensional arrays, it's often easier to work in component form. Consider the following function:

Ω = sum(abs2, X::Array{<:RealOrComplex,3}; dims=2)::Array{<:Real,3}

which we write as

$$$\Omega_{i1k} = \sum_{j} |X_{ijk}|^2 = \sum_{j} \Re \ip{X_{ijk}}{X_{ijk}}$$$

The pushforward from \eqref{pf} is

\begin{align} \dot{\Omega}_{i1k} &= \sum_j \Re\ip{\dot{X}_{ijk}}{X_{ijk}} + \ip{X_{ijk}}{\dot{X}_{ijk}} \nonumber\\ &= \sum_j \Re\ip{X_{ijk}}{\dot{X}_{ijk}}^* + \ip{X_{ijk}}{\dot{X}_{ijk}} \nonumber\\ &= \sum_j 2 \Re\ip{X_{ijk}}{\dot{X}_{ijk}}, \label{sumabspf} \end{align}

where in the last step we have used the fact that for all real $a$ and $b$,

$$$(a + i b) + (a + i b)^* = (a + i b) + (a - i b) = 2 a = 2 \Re (a + i b).$$$

Because none of this derivation depended on the index (or indices), we implement frule generically as

function frule(
(_, _, ΔX),
::typeof(sum),
::typeof(abs2),
X::Array{<:RealOrComplex};
dims = :,
)
Ω = sum(abs2, X; dims = dims)
∂Ω = sum(2 .* real.(conj.(X) .* ΔX); dims = dims)
return (Ω, ∂Ω)
end

We can now derive the reverse-mode rule. The elementwise form of \eqref{pbident} is

\begin{align*} \Re\ip{ \overline{\Omega} }{ \dot{\Omega} } &= \Re \left( \sum_{ik} \overline{\Omega}_{i1k}^* \dot{\Omega}_{i1k} \right) && \text{expand left-hand side of } \eqref{pbident}\\ &= \Re \left(\sum_{ijk} \overline{\Omega}_{i1k}^* 2 \Re\left( X_{ijk}^* \dot{X}_{ijk} \right) \right) && \text{substitute } \eqref{sumabspf}\\ &= \Re \left( \sum_{ijk} \left( 2 \Re \left( \overline{\Omega}_{i1k} \right) X_{ijk}^* \right) \dot{X}_{ijk} \right) && \text{bring } \dot{X}_{ijk} \text{ outside of } \Re\\ &= \sum_{ijk} \Re\ip{2 \Re \left( \overline{\Omega}_{i1k} \right) X_{ijk}}{\dot{X}_{ijk}} && \text{rewrite as an inner product}\\ &= \sum_{ijk} \Re\ip{\overline{X}_{ijk}}{\dot{X}_{i1k}} && \text{right-hand side of } \eqref{pbident} \end{align*}

We now solve for $\overline{X}$:

$$$\overline{X}_{ijk} = 2\Re \left( \overline{\Omega}_{i1k} \right) X_{ijk}$$$

Like the frule, this rrule can be implemented generically:

function rrule(::typeof(sum), ::typeof(abs2), X::Array{<:RealOrComplex}; dims = :)
function sum_abs2_pullback(ΔΩ)
∂abs2 = NoTangent()
∂X = @thunk(2 .* real.(ΔΩ) .* X)
return (NoTangent(), ∂abs2, ∂X)
end
return sum(abs2, X; dims = dims), sum_abs2_pullback
end

## Functions that return a tuple

Every Julia function returns a single output. For example, let's look at LinearAlgebra.logabsdet, the logarithm of the absolute value of the determinant of a matrix, which returns $\log |\det(A)|$ and $\operatorname{sign}(\det A) = \frac{\det A}{| \det A |}$:

(l, s) = logabsdet(A)

The return type is actually a single output, a tuple of scalars, but when deriving, we treat them as multiple outputs. The left-hand side of \eqref{pbident} then becomes a sum over terms, just like the right-hand side.

Let's derive the forward- and reverse-mode rules for logabsdet.

\begin{align*} l &= \log |\det(A)|\\ s &= \operatorname{sign}(\det(A)), \end{align*}

where $\operatorname{sign}(x) = \frac{x}{|x|}$.

### Forward-mode rule

To make this easier, let's break the computation into more manageable steps:

\begin{align*} d &= \det(A)\\ a &= |d| = \sqrt{\Re \left( d^* d \right)}\\ l &= \log a\\ s &= \frac{d}{a} \end{align*}

We'll make frequent use of the identities:

$$$d = a s$$$$$$s^* s = \frac{d^* d}{a^2} = \frac{a^2}{a^2} = 1$$$

It will also be useful to define $b = \tr\left( A^{-1} \dot{A} \right)$.

For $\dot{d}$, we use the pushforward for the determinant given in section 2.2.4 of [Giles2008ext]:

$$$\dot{d} = d b$$$

Now we'll compute the pushforwards for the remaining steps.

\begin{align*} \dot{a} &= \frac{1}{2 a} \frac{d}{dt} \Re\left( d^* d \right)\\ &= \frac{2}{2 a} \Re \left( d^* \dot{d} \right)\\ &= \Re \left( s^* \dot{d} \right) && \text{use } d = a s \\ &= \Re \left( s^* d b \right) && \text{substitute } \dot{d} \\ \dot{l} &= a^{-1} \dot{a}\\ &= a^{-1} \Re \left( s^* d b \right) && \text{substitute } \dot{a}\\ &= \Re \left( s^* s b \right) && \text{use } d = a s \\ &= \Re \left(b \right) && \text{use } s^* s = 1\\ \dot{s} &= a^{-1} \dot{d} - a^{-2} d \dot{a}\\ &= a^{-1} \left( \dot{d} - \dot{a} s \right) && \text{use } d = a s \\ &= a^{-1} \left( \dot{d} - \Re \left( s^* \dot{d} \right) s \right) && \text{substitute } \dot{a}\\ &= a^{-1} \left( \dot{d} - \left( s^* \dot{d} - i \Im \left( s^* \dot{d} \right) \right) s \right) && \text{use } \Re(x) = x - i \Im(x)\\ &= a^{-1} \left( \dot{d} - \left( s^* s \right) \dot{d} + i \Im \left( s^* \dot{d} \right) s \right)\\ &= i a^{-1} \Im \left( s^* \dot{d} \right) s && \text{use } s^* s = 1\\ &= i a^{-1} \Im \left( s^* d b \right) s && \text{substitute } \dot{d}\\ &= i \Im \left( s^* s b \right) s && \text{use } d = a s \\ &= i \Im(b) s && \text{use } s^* s = 1 \end{align*}

Note that the term $b$ is reused. In summary, after all of that work, the final pushforward is quite simple:

\begin{align} b &= \tr \left( A^{-1} \dot{A} \right) \label{logabsdet_b} \\ \dot{l} &= \Re(b) \label{logabsdet_ldot}\\ \dot{s} &= i \Im(b) s \label{logabsdet_sdot}\\ \end{align}

We can define the frule as:

function frule((_, ΔA), ::typeof(logabsdet), A::Matrix{<:RealOrComplex})
# The primal function uses the lu decomposition to compute logabsdet
# we reuse this decomposition to compute inv(A) * ΔA
F = lu(A, check = false)
Ω = logabsdet(F)  # == logabsdet(A)
b = tr(F \ ΔA)  # == tr(inv(A) * ΔA)
s = last(Ω)
∂l = real(b)
# for real A, ∂s will always be zero (because imag(b) = 0)
# this is type-stable because the eltype is known
∂s = eltype(A) <: Real ? ZeroTangent() : im * imag(b) * s
# tangents of tuples are of type Tangent{<:Tuple}
∂Ω = Tangent{typeof(Ω)}(∂l, ∂s)
return (Ω, ∂Ω)
end

### Reverse-mode rule

\begin{align*} &\Re\ip{\overline{l}}{\dot{l}} + \Re\ip{\overline{s}}{\dot{s}} && \text{left-hand side of } \eqref{pbidentmat}\\ &= \Re\left( \overline{l}^* \dot{l} + \overline{s}^* \dot{s} \right) \\ &= \Re\left( \overline{l}^* \Re(b) + i \overline{s}^* s \Im(b) \right) && \text{substitute } \eqref{logabsdet_ldot} \text{ and } \eqref{logabsdet_sdot} \\ &= \Re\left( \Re\left( \overline{l} \right) \Re(b) - \Im \left( \overline{s}^* s \right) \Im(b) \right) && \text{discard imaginary parts} \\ &= \Re\left( \left( \Re \left( \overline{l} \right) + i \Im \left( \overline{s}^* s \right) \right) b \right) && \text{gather parts of } b \\ &= \Re\left( \left( \Re \left( \overline{l} \right) + i \Im \left( \overline{s}^* s \right) \right) \tr(A^{-1} \dot{A}) \right) && \text{substitute } b \text{ from } \eqref{logabsdet_b} \\ &= \Re\left( \tr \left( \left( \Re \left( \overline{l} \right) + i \Im \left( \overline{s}^* s \right) \right) A^{-1} \dot{A} \right) \right) && \text{bring scalar within } \tr \\ &= \Re\ip{ \left( \Re \left( \overline{l} \right) + i \Im \left( s^* \overline{s} \right) \right) A^{-\mathsf{H}} }{\dot{A}} && \text{rewrite as inner product}\\ &= \Re\ip{\overline{A}}{\dot{A}} && \text{right-hand side of } \eqref{pbidentmat}\\ \end{align*}

Now we solve for $\overline{A}$:

\begin{align*} \overline{A} = \left( \Re \left( \overline{l} \right) + i \Im \left( s^* \overline{s} \right) \right) A^{-\mathsf{H}} \end{align*}

The rrule can be implemented as

function rrule(::typeof(logabsdet), A::Matrix{<:RealOrComplex})
# The primal function uses the lu decomposition to compute logabsdet
# we reuse this decomposition to compute inv(A)
F = lu(A, check = false)
Ω = logabsdet(F)  # == logabsdet(A)
s = last(Ω)
function logabsdet_pullback(ΔΩ)
(Δl, Δs) = ΔΩ
f = conj(s) * Δs
imagf = f - real(f)  # 0 for real A and Δs, im * imag(f) for complex A and/or Δs
g = real(Δl) + imagf
∂A = g * inv(F)'  # == g * inv(A)'
return (NoTangent(), ∂A)
end
return (Ω, logabsdet_pullback)
end
Note

It's a good idea when deriving pushforwards and pullbacks to verify that they make sense. For the pushforward, since $l$ is real, it follows that $\dot{l}$ is too.

What about $\dot{s}$? Well, $s = \frac{d}{|d|}$ is point on the unit circle in the complex plane. Multiplying a complex number by $i$ rotates it counter-clockwise by 90°. So the expression for $\dot{s}$ takes a real number, $\Im(b)$, multiplies by $s$ to make it parallel to $s$, then multiplies by $i$ to make it perpendicular to $s$, that is, perfectly tangent to the unit complex circle at $s$.

For the pullback, it again follows that only the real part of $\overline{l}$ is pulled back.

$s^*$ rotates a number parallel to $s$ to the real line. So $s^* \overline{s}$ rotates $\overline{s}$ so that its imaginary part is the part that was tangent to the complex circle at $s$, while the real part is the part that was not tangent. Then the pullback isolates the imaginary part, which effectively is a projection. That is, any part of the adjoint $\overline{s}$ that is not tangent to the complex circle at $s$ will not contribute to $\overline{A}$.

## Implicit functions

Sometimes a function is only defined implicitly, and internally some solver or iterative algorithm is used to compute the result. We can still in some cases derive rules by considering only the implicit functions and not the internals. One example is the solution $X$ to the Sylvester equation

$$$A X + X B = -C$$$

for inputs $A$, $B$, and $C$. We can also write this solution as $X = \operatorname{sylvester}(A, B, C)$, which in Julia is computed using LinearAlgebra.sylvester(A, B, C).

### Forward-mode Rule

We start by differentiating the implicit function:

$$$\dot{A} X + A \dot{X} + \dot{X} B + X \dot{B} = -\dot{C}$$$

Then we isolate the terms with $\dot{X}$ on one side:

\begin{align} A \dot{X} + \dot{X} B &= -\dot{C} - \dot{A} X - X \dot{B} \label{sylpfimplicit}\\ &= -(\dot{C} + \dot{A} X + X \dot{B}) \nonumber \end{align}

So the pushforward is the solution to a different Sylvester equation:

$$$\dot{X} = \operatorname{sylvester}(A, B, \dot{C} + \dot{A} X + X \dot{B})$$$

The frule can be implemented as

function frule((_, ΔA, ΔB, ΔC), ::typeof(sylvester), A, B, C)
X = sylvester(A, B, C)
return X, sylvester(A, B, ΔC + ΔA * X + X * ΔB)
end

### Reverse-mode Rule

Like with the pushforward, it's easiest to work with the implicit function. We start by introducing some dummy $-Z$ and taking its inner product with both sides of \eqref{sylpfimplicit}:

$$$\ip{-Z}{A \dot{X} + \dot{X} B} = \ip{-Z}{-\dot{C} - \dot{A} X - X \dot{B}}.$$$

Then we expand

$$$\ip{-Z}{A \dot{X}} + \ip{-Z}{\dot{X} B} = \ip{Z}{\dot{C}} + \ip{Z}{\dot{A} X} + \ip{Z}{X \dot{B}}.$$$

Now permute:

$$$\ip{-A^\mathsf{H} Z}{\dot{X}} + \ip{-Z B^\mathsf{H}}{\dot{X}} = \ip{Z}{\dot{C}} + \ip{Z X^\mathsf{H}}{\dot{A}} + \ip{X^\mathsf{H} Z}{X \dot{B}}.$$$

Then combine:

$$$\ip{-(A^\mathsf{H} Z + Z B^\mathsf{H})}{\dot{X}} = \ip{Z X^\mathsf{H}}{\dot{A}} + \ip{X^\mathsf{H} Z}{X \dot{B}} + \ip{Z}{\dot{C}}.$$$

This is almost exactly the identity we need to solve for $\overline{A}$, $\overline{B}$, and $\overline{C}$. To manipulate it to the right form, we need only define $A^\mathsf{H} Z + Z B^\mathsf{H} = -\overline{X}$. This yet another Sylvester equation, so letting $Z = \overline{C}$, our final pullback is:

\begin{align*} \overline{C} &= \operatorname{sylvester}(A^\mathsf{H}, B^\mathsf{H}, \overline{X})\\ &= \operatorname{sylvester}(B, A, \overline{X}^\mathsf{H})^\mathsf{H}\\ \overline{A} &= \overline{C} X^\mathsf{H}\\ \overline{B} &= X^\mathsf{H} \overline{C}\\ \end{align*}

The rrule can be implemented as

function rrule(::typeof(sylvester), A, B, C)
X = sylvester(A, B, C)
function sylvester_pullback(ΔX)
∂C = copy(sylvester(B, A, copy(ΔX'))')
return NoTangent(), @thunk(∂C * X'), @thunk(X' * ∂C), ∂C
end
return X, sylvester_pullback
end

Note, however, that the Sylvester equation is usually solved using the Schur decomposition of $A$ and $B$. These Schur decompositions can be reused to solve the Sylvester equations in the pushforward and pullback. See the implementation in ChainRules for details.

## More examples

For more instructive examples of array rules, see [Giles2008ext] (real vector and matrix rules) and the LinearAlgebra rules in ChainRules. For differentiating the LU decomposition, see this blog post by Seth Axen.

• Giles2008

Giles M. B. Collected Matrix Derivative Results for Forward and Reverse Mode Algorithmic Differentiation. In: Advances in Automatic Differentiation. Lecture Notes in Computational Science and Engineering, vol 64: pp 35-44. Springer, Berlin (2008). doi: 10.1007/978-3-540-68942-3_4. pdf

• Giles2008ext

Giles M. B. An Extended Collection of Matrix Derivative Results for Forward and Reverse Mode Algorithmic Differentiation. (unpublished). pdf